Pendekatan Pemberdayaan Dalam Penanganan Permukiman Squatter: Sebuah Evaluasi Empiris - Hudalah, Delik (Journal of Regional and City Planning, 2005)
Empowerment  approaches  in  order to alleviate poverty  and  promote  sustainable development are not new and still need further  research on the  concept, planning, and implementation.  Involving  the  World  Bank  and  other  non -government institutions, the Government of Indonesia since 2003 develop ed  those approaches which  are  more  integrated  and  participative  through  Squatter  Settlemen its Pilot Assistance  Project  (PPM-Squatter).  This  paper  critiques  and  corrects  the domination  of  those  non -government  institutions  in  financing  and  assisting  the project/program. This paper also shows factors that  determine the performance of empowerment  ap proaches  in  squatter  settlements  assistance,  which  are  (1) interpretation  of  concept  of  the  program  and  typology  of  squatter,  (2)  political absorption by government institutions in all level, and (3) facilitation, monitoring and evaluation.Keywords: empowerment approach, squatter settlement assistance, empirical evaluation